2016
DOI: 10.1097/mao.0000000000000942
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Success

Abstract: Only a small fraction of patients with profound sensorineural hearing loss have access to cochlear implantation with the majority of these affected people living in developing countries. Cost effectiveness analysis (CEA) is an important tool to demonstrate the value of this technology to healthcare policy makers. This approach requires that hearing healthcare professionals incorporate methods of assessing long-term benefits of cochlear implantation that include psychosocial, quality of life, and disability out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The cost-effectiveness of cochlear implants has been established in developed countries 71 and in some developing countries. 71,7477 These analyses have evaluated the lifetime costs of cochlear implants, including the costs of the device and of surgery and rehabilitation, versus the benefits, as determined on the basis of health-preference measures. Measures of cost-effectiveness have also been used to compare cochlear implants with other treatments, such as educational programs for deaf persons, and these assessments have shown that cochlear implants compare favorably with other treatments.…”
Section: Treatment Of Sensorineural Hearing Lossmentioning
confidence: 99%
“…The cost-effectiveness of cochlear implants has been established in developed countries 71 and in some developing countries. 71,7477 These analyses have evaluated the lifetime costs of cochlear implants, including the costs of the device and of surgery and rehabilitation, versus the benefits, as determined on the basis of health-preference measures. Measures of cost-effectiveness have also been used to compare cochlear implants with other treatments, such as educational programs for deaf persons, and these assessments have shown that cochlear implants compare favorably with other treatments.…”
Section: Treatment Of Sensorineural Hearing Lossmentioning
confidence: 99%
“…functioning and can lead to cognitive decline [32]. Cochlear Implants (CI) restore access to sound and improve social function for most profoundly deaf listeners [33][34][35]. However, not all CI users perform well in the real world and there is substantial unexplained variability in outcomes [36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Although the CI has been evaluated as cost-effective in some middleincome countries (12), the policy benefits in Chile need to be assessed in detail. Inequalities, lack of funding and social protection programs might influence cost-effectiveness (45).…”
Section: Discussionmentioning
confidence: 99%